Relación entre gasto del ministerio de producción y la creación de MYPES en la región de loreto periodo 2007 – 2022 - Panduro Gomez, Hingryd Nathaly (2025)
This research analyzes the relationship between the Ministry of Production's expenditure and the creation of MSEs (micro and small enterprises) in the Loreto region during the 2007-2022 period, aiming to assess the impact of public policies on business development. Using a quantitative, descriptive, and correlational design, historical data on public spending and the number of MSEs were analyzed, applying statistical tools such as the Spearman correlation coefficient to validate the proposed hypotheses. The results show a positive and statistically significant relationship between public spending and MSE creation, with a stronger connection in specific components such as technological development and innovation. However, the overall intensity of the relationship is moderate, revealing limitations in spending effectiveness to overcome structural barriers such as insufficient infrastructure and limited market access. The discussion links these findings to previous studies, highlighting the need for more targeted and regionally adapted policies. The conclusions emphasize the importance of strengthening strategic planning, decentralizing management, and prioritizing training and technological innovation to maximize the impact of public spending on entrepreneurship. This study provides a foundation for designing more effective interventions at the regional level.